Analysis of Student Learning Difficulties in PAI Subjects in Class XI of SMAN 5 Palangka Raya - Mega Selfia; Ikbal Lupariq (Institut Agama Islam Al-Quran Al-Ittifaqiah (IAIQI) Indralaya, 2024)
This research aims to 1) find out whether PAI subjects are difficult for students to understand; 2) knowing what PAI material is difficult for students to experience; 3) knowing the difficulties experienced by students in understanding PAI subject matter which is difficult for them; 4) know the learning media that are often used in the learning process at school; 5) state the learning media that need to be used to help students’ difficulties in understanding difficult PAI subject matter. This type of research is (R&D) using 3D research methods (define, design, develop). This research is only at the define stage. In the data collection process, the method used was to distribute an online questionnaire in Google Form format to subjects or class XI students at SMAN 5 Palangka Raya via the social media WhatsApp. The results of the questionnaire collection concluded that 1) some students thought that PAI subjects were difficult. 2) some students think they find difficulties in PAI lesson material, namely about the glory days of Islam. 3) some students believe that they have difficulty understanding PAI material, especially during the heyday of Islam, because the material is difficult and complicated, and there is a lack of variety of media for understanding the material. 4) students think that the media most often used in school is textbooks/LKS. 5) as many as 46.3% of students agreed to use PPT-based media and students thought that using PPT-based media was interesting and varied in understanding PAI subject matter.